Association between changes in swimming velocity, vertical center of mass position, and projected frontal area during maximal 200-m front crawl - Washino, S.; Murai, A.; Mankyu, H.; Yoshitake, Y. (Proceedings, 2020)
We examined the association between changes in swimming velocity, vertical center of mass (CoM) position, and projected frontal area (PFA) during maximal 200-m front crawl. Three well-trained male swimmers performed a single maximal 200-m front crawl in an indoor 25-m pool. Three-dimensional (3D) shape data of the whole body were fitted to 3D motion data during swimming by using inverse kinematics computation to estimate PFA accurately. Swimming velocity decreased, the vertical CoM position was lowered, and PFA increased with swimming distance. There were significant correlations between swimming velocity and vertical CoM position (|r| = 0.797-0.982) and between swimming velocity and PFA (|r| = 0.716-0.884) for each swimmer. These results suggest that descent of the swimmer`s body and increasing PFA with swimming distance are associated with decreasing swimming velocity, although the causal factor remains unclear.